Nectaries and reproductive biology of Croton sarcopetalus (Euphorbiaceae) - Freitas, L.; Bernardello, G.; Galetto, L.; Paoli, Adelita Aparecida Sartori [UNESP] (Academic Press Ltd, 2001)
Flower morphology, nectary structure, nectar chemical composition, breeding system, floral visitors and pollination were analysed in Croton sarcopetalus, a diclinous-monoecious shrub from Argentina. Male flowers have five receptacular nectaries, with no special vascular bundles, that consist of a uniserial epidermis with stomata subtended by a secretory parenchyma. Female flowers bear two different types of nectaries: inner (IN) and outer (ON) floral nectaries. IN, five in all, are structurally similar to the nectaries of male flowers. The five ON are vascularized, stalked, and composed of secretory, column-shaped epidermal cells without stomata subtended by secretory and ground parenchyma. In addition, ON act as post-floral nectaries secreting nectar during fruit ripening. Extrafloral nectaries (EFN) are located on petioles, stipules and leaf margins. Petiolar EFN are patelliform, stalked and anatomically similar to the ON of the female flower. Nectar sampled from all nectary types is hexose dominant, except for the ON of the female flower at the post-floral stage that is sucrose dominant. The species is self-compatible, but geitonogamous fertilization is rarely possible because male and female flowers are not usually open at the same time in the same individual, i.e. there is temporal dioecism. Flowers are visited by 22 insect species, wasps being the most important group of pollinators. No significant differences were found in fruit and seed set between natural and hand pollinated flowers. This pattern indicates that fruit production in this species is not pollen/pollinator limited and is mediated by a wide array of pollinators. (C) 2001 the Linnean Society of London.
Keywords: extrafloral nectaries; floral nectaries; insect pollination; nectar chemical composition; post-floral nectaries; self-compatibility; temporal dioecism